PERANAN ASSET NAFKAH TERHADAP STRATEGI NAFKAH RUMAH TANGGA PETANI GUREM LAHAN KERING DI KECAMATAN CAMBA KABUPATEN MAROS - Aulia Nurul Hikmah; Muhammad Dassir; Sitti Nadira (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Nationally, the large number of smallholders in Indonesia with small land tenure, individual and traditional management patterns have prevented Indonesian agriculture from reaching the desired economic scale. Based on this aim of this study was to determine the livelihoods and livelihood strategies of dryland smallholders. The results show that the livelihood assets that play an important role in the livelihood strategy of smallholders are the social capital of land tenure in the form of acquisition of teseng land and sanra land (land pledge agreements) to conduct agricultural activities and implement livelihood strategies. Livelihood strategies carried out by smallholders in drylands are mostly still in the agricultural (off-farm) sector, namely the strategy of intensification of agricultural land by diversifying cropping patterns in paddy fields and land. in the dry season by planting seasonal crops on dry land. like peanuts. To maintain a year of food subsistence and increase the economic resilience of smallholders, they are implementing a dual livelihood strategy in the non-agricultural sector, such as space engineering by migrating gardening to other provinces. One of the activities of the smallholder dual income strategy is to develop a cocoa plantation and become a construction worker for a project in their village which is a non-farm sector activity. A forward-looking sustainable livelihood strategy for smallholders is through the development of intensive agroforestry diversification by planting legumes, peppers, tomatoes and ginger.